IGZO target material with high density, high conductivity and low resistivity and preparation method thereof

By adding specific chemical substances and modified surfactants to the powder slurry of IGZO targets, and using ultrasonic bombardment and precise sintering technology, the problem of insufficient conductivity and density of traditional IGZO targets is solved, and the preparation of target materials with high density, high conductivity and low resistivity is achieved.

CN119613093AInactive Publication Date: 2025-03-14WUHU YINGRI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510147506.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional IGZO targets have poor electrical conductivity and density, making it difficult to meet the needs of high-performance electronic devices.

Method used

By adding enzyme polymerized lignosulfonic acid and 1,2,3,4-butanetetracarboxylic acid to the powder slurry, and using modified surfactant and ultrasonic bombardment technology, the sintering parameters are accurately regulated during the sintering process to form high-density, high conductivity, and low resistivity IGZO targets.

Benefits of technology

It significantly improves the density and conductivity of IGZO targets, maintains a small grain size, and is suitable for the manufacturing of high-performance electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of target material manufacturing, in particular to a high-density, high-conductivity and low-resistivity IGZO target material and a preparation method thereof. The invention discloses a preparation method of a high-density, high-conductivity and low-resistivity IGZO target material. The preparation method comprises the following steps: preparing a modified surfactant, preparing In2O3 powder, Ga2O3 powder and ZnO powder, preparing mixed slurry, wet-grinding the slurry, granulating, pressing and sintering. The IGZO target material has the characteristics of high density, high conductivity and low resistivity by adding a modified surfactant into the mixed slurry, applying ultrasonic treatment in the wet grinding process and accurately regulating and controlling sintering parameters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of target material manufacturing, and in particular to a high-density, high-conductivity, low-resistivity IGZO target material and a preparation method thereof. Background Art

[0002] With the rapid development of electronic information industries such as flat panel displays, flexible electronic devices, and touch screens, the demand for high-performance oxide semiconductor materials is increasing. IGZO (In-Ga-Zn-O), as a new type of oxide semiconductor material, has become an ideal material for TFT devices because of its following advantages: High carrier mobility: Compared with traditional amorphous silicon (a-Si), IGZO has higher carrier mobility, which can achieve higher device switching speeds and lower operating voltages; High transparency: IGZO films have high transparency in the visible light range and are suitable for manufacturing transparent display devices; Low power consumption: IGZO devices have lower leakage current and power consumption, which is conducive to extending battery life; Large area uniformity: IGZO films have good uniformity and consistency, which is suitable for large-area manufacturing.

[0003] Patent technical document CN117105636A discloses a method for preparing an IGZO target material. The invention realizes the preparation of an IGZO target material with high density and low warpage by finely controlling the material ratio, ball milling and sand milling processes, applying appropriate pressure, and optimizing the preparation process. The specific steps include ball milling indium oxide powder, gallium oxide powder, zinc oxide powder, and deionized water, adding a dispersant, a defoaming agent, and deionized water for sand milling, and then granulating and sintering the powder. The IGZO target material obtained by the invention has high density and low warpage, and is suitable for various application fields, such as displays and thin film transistors. However, when it is used for magnetron sputtering, its conductive properties need to be further improved. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a high-density, high-conductivity, low-resistivity IGZO target material and a preparation method thereof, so as to solve the problems of poor conductivity and density of traditional IGZO target materials.

[0005] Based on the above purpose, the present invention provides a method for preparing a high-density, high-conductivity, and low-resistivity IGZO target, comprising the following steps: (1) dissolving sodium lignin sulfonate in deionized water and adjusting the pH to 7 to obtain a sodium lignin sulfonate solution, then adding laccase, stirring at 500-600 rpm in an air atmosphere at 37-40° C., continuously detecting during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonate reaches 750-770 kDa, terminating the reaction, purifying, and obtaining the enzyme-polymerized lignin sulfonate; (2) Enzyme-polymerized lignosulfonic acid, 1,2,3,4-butanetetracarboxylic acid and N,N-dimethylformamide were mixed, stirred evenly, and N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added, reacted at room temperature for 48 hours, filtered, precipitated in 1M HCl aqueous solution, filtered, and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc are placed in a plasma reactor respectively, and In is prepared by a DC plasma method. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, after drying, depolymerization to obtain In 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 Powder,Ga 2 O 3 The powder and ZnO powder are mixed, deionized water and dispersant are added, stirred evenly, and then 0.5-2.5 g of modified surfactant is added, and the mixture is allowed to stand for 1-2 h to obtain a mixed slurry; (5) placing the mixed slurry in a horizontal high-energy sand mill for wet grinding, and applying ultrasonic bombardment of 2000 W power to the slurry in the grinding chamber during the grinding process to obtain a composite slurry; (6) spray granulating the composite slurry to obtain IGZO powder; (7) Putting IGZO powder into a mold and pressing it to obtain a blank; (8) Sintering the green blank, first heating the temperature from room temperature to 700-750°C at a heating rate of 2-3°C / min, then heating the temperature to 1000-1100°C at a heating rate of 1-1.5°C / min, then sintering to 1320-1350°C at a heating rate of 0.7-0.9°C / min, keeping the temperature for 20-22h, and finally cooling the temperature from 1320-1350°C to room temperature at a cooling rate of 3-4°C / min, wherein oxygen is introduced at a flow rate of 10 L / min at 0-1100°C, air is introduced at a flow rate of 5 L / min at 1100-1350°C, and air is introduced at a flow rate of 20 L / min when cooling from 1350°C to room temperature. L / min nitrogen; the dosage ratio of the sodium lignin sulfonate solution and laccase in step (1) is 100ml:330-340ml; the dosage ratio of the enzyme-polymerized lignin sulfonic acid, 1,2,3,4-butanetetracarboxylic acid, N,N-dimethylformamide, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step (2) is 5-10g:1-2g:200-250ml:10-15g:2-3g.

[0006] Preferably, the concentration of the sodium lignin sulfonate solution in step (1) is 20%-25%.

[0007] Preferably, the parameters of the DC plasma method in step (3) are as follows: high-purity argon atmosphere, high-purity oxygen is introduced, the oxygen flow rate is controlled to be 30-40 sccm, 100-200A of DC power is applied, and the temperature is 1000-1500°C.

[0008] Preferably, the depolymerization in step (3) is carried out by using air flow pulverization technology, which can avoid the impurity contamination problem caused by traditional mechanical grinding.

[0009] Preferably, in step (4), 2 O 3 Powder,Ga 2 O 3 The added amounts of powder and ZnO powder are based on a molar ratio of indium, gallium and zinc of 1:1:1.

[0010] Preferably, the dispersant in step (4) is one of polyvinyl alcohol and polyethylene glycol, and the added amount is 0.1%-0.25% of deionized water. The modified surfactant in step (4) is added in an amount of 0.1%-0.5% of deionized water.

[0011] Preferably, the ball milling speed of the wet grinding in step (5) is 800-1000 rpm, and the ball milling time is 2-3 h.

[0012] Preferably, the parameters of the spray granulation in step (6) are: atomizing disk speed 7500-8000 rpm, air inlet temperature 250-260°C, and air outlet temperature 110-120°C.

[0013] Preferably, the pressing pressure in step (7) is 200-300 MPa.

[0014] Furthermore, the present invention also provides a high-density, high-conductivity, low-resistivity IGZO target material, and the high-density, high-conductivity, low-resistivity IGZO target material is prepared according to the above-mentioned high-density, high-conductivity, low-resistivity IGZO target material preparation method.

[0015] Beneficial effects of the present invention: The high-density, high-conductivity, low-resistivity IGZO target material of the present invention is prepared by adding enzyme-polymerized lignosulfonic acid and 1,2,3,4-butanetetracarboxylic acid into the powder slurry, and the two can interact with each other on the powder surface, so that the density and conductivity of the target material are significantly improved, and the grain size is maintained in a smaller range.

[0016] The high-density, high-conductivity, low-resistivity IGZO target material of the present invention combines the steric hindrance effect of enzyme-polymerized lignosulfonic acid and the multi-functional characteristics of 1,2,3,4-butanetetracarboxylic acid by adding a modified surfactant into the slurry, and can form a more stable adsorption layer on the particle surface, providing a stronger dual effect of electrostatic repulsion and steric hindrance, thereby achieving a better dispersion effect, so that the density and conductivity of the target material are further improved, and a smaller grain size can also be maintained.

[0017] The high-density, high-conductivity, low-resistivity IGZO target material of the present invention can produce a certain synergistic effect with the modified surfactant by adding ultrasonic bombardment treatment during the wet grinding process, so that the conductive performance, density and small grain size of the target material are guaranteed.

[0018] The high-density, high-conductivity, low-resistivity IGZO target material of the present invention further accurately regulates the sintering parameters during the sintering process, so that the conductivity, density and small grain size of the target material are all at a relatively excellent level. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0020] Example 1: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 20% sodium lignin sulfonate solution. Then add 330 ml of laccase, stir at 500 rpm in an air atmosphere at 37° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 750 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) 5 g of enzyme-polymerized lignosulfonic acid, 1 g of 1,2,3,4-butanetetracarboxylic acid and 200 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 10 g of N,N'-dicyclohexylcarbodiimide and 2 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 30 sccm, a direct current of 100 A was applied, and In was prepared at 1000 °C. 2 O 3 Powder, Ga 2 O 3Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 40nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 , Ga 2 O 3 , ZnO powders were mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 0.5 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 50%, and then 0.5 g of a modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 1 hour, and the mixture was put into a horizontal high-energy sand mill and ground at 800 rpm for 2 hours for wet grinding. During the grinding process, the slurry in the grinding chamber was subjected to ultrasonic bombardment with a power of 2000 W to obtain a composite slurry; (5) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7500 rpm, the inlet air temperature of 250°C, and the outlet air temperature of 110°C to obtain IGZO powder; (6) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 200 MPa; (7) The green embryo was sintered by first heating the temperature from room temperature to 700 °C at a heating rate of 2 °C / min, then heating the temperature to 1000 °C at a heating rate of 1 °C / min, and then sintering to 1320 °C at a heating rate of 0.7 °C / min, keeping the temperature for 20 h, and finally cooling the temperature from 1320 °C to room temperature at a cooling rate of 3 °C / min. In the range of 0-1100 °C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350 °C, air was introduced at a flow rate of 5 L / min. When cooling from 1350 °C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0021] Example 2: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 23% sodium lignin sulfonate solution. Then add 335 ml of laccase, stir at 550 rpm in an air atmosphere at 38° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 760 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) 8 g of enzyme-polymerized lignosulfonic acid, 1.5 g of 1,2,3,4-butanetetracarboxylic acid and 230 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 13 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, and a direct current of 150 A was applied to prepare In at 1300 °C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 , Ga 2 O 3 , ZnO powder was mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%, and then 1.5 g of a modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 2 h, and the mixture was put into a horizontal high-energy sand mill and ground at 900 rpm for 3 h for wet grinding. During the grinding process, the slurry in the grinding chamber was subjected to ultrasonic bombardment with a power of 2000 W to obtain a composite slurry; (5) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (6) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (7) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0022] Embodiment 3: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 25% sodium lignin sulfonate solution. Then add 340 ml of laccase, stir at 600 rpm in an air atmosphere at 40° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 770 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) 10 g of enzyme-polymerized lignosulfonic acid, 2 g of 1,2,3,4-butanetetracarboxylic acid and 250 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 15 g of N,N'-dicyclohexylcarbodiimide and 3 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc were placed in a plasma reactor respectively, and high-purity oxygen was introduced into the reactor under a high-purity argon atmosphere. The oxygen flow rate was controlled to be 40 sccm, and a direct current of 200 A was applied to prepare In at 1500°C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 50nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 , Ga 2 O 3 , ZnO powder was mixed according to the molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1.25 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 70%, and then 2.5 g of modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 2 hours, and the mixture was put into a horizontal high-energy sand mill and ground at 1000 rpm for 3 hours for wet grinding. During the grinding process, the slurry in the grinding chamber was subjected to ultrasonic bombardment with a power of 2000 W to obtain a composite slurry; (5) The composite slurry was sprayed and granulated, with the atomizing disk speed of 8000 rpm, the inlet air temperature of 260°C, and the outlet air temperature of 120°C to obtain IGZO powder; (6) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 300 MPa; (7) The green embryo was sintered by first heating the temperature from room temperature to 750°C at a heating rate of 3°C / min, then heating the temperature to 1100°C at a heating rate of 1.5°C / min, and then sintering to 1350°C at a heating rate of 0.9°C / min, keeping the temperature for 22 h, and finally cooling the temperature from 1350°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0023] Comparative Example 1: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, a direct current of 150 A was applied, and In was prepared at 1300 °C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (2) In 2 O 3 , Ga 2 O 3 , ZnO powder was mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%. The mixture was stirred evenly and allowed to stand for 2 hours, and then placed in a horizontal high-energy sand mill and ground at 900 rpm for 3 hours for wet grinding. During the grinding process, ultrasonic bombardment with a power of 2000 W was applied to the slurry in the grinding chamber to obtain a composite slurry; (3) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (4) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (5) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0024] Comparative Example 2: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 23% sodium lignin sulfonate solution. Then add 335 ml of laccase, stir at 550 rpm in an air atmosphere at 38° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 760 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, and a direct current of 150 A was applied to prepare In at 1300 °C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (3) In 2 O 3 , Ga 2 O 3 , ZnO powders were mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%, and then 1.26 g of enzyme-polymerized lignosulfonic acid and 0.24 g of 1,2,3,4-butanetetracarboxylic acid were added, and the mixture was stirred evenly and allowed to stand for 2 h, and the mixture was placed in a horizontal high-energy sand mill and ground at 900 rpm for 3 h for wet grinding, and during the grinding process, ultrasonic bombardment with a power of 2000 W was applied to the slurry in the grinding chamber to obtain a composite slurry; (4) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (5) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (6) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0025] Comparative Example 3: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) 8 g of sodium lignin sulfonate, 1.5 g of 1,2,3,4-butanetetracarboxylic acid and 230 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 13 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (2) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, and a direct current of 150 A was applied to prepare In at 1300 °C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (3) In 2 O 3 , Ga 2 O 3, ZnO powder was mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%, and then 1.5 g of a modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 2 h, and the mixture was put into a horizontal high-energy sand mill and ground at 900 rpm for 3 h for wet grinding. During the grinding process, the slurry in the grinding chamber was subjected to ultrasonic bombardment with a power of 2000 W to obtain a composite slurry; (4) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (5) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (6) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0026] Comparative Example 4: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 23% sodium lignin sulfonate solution. Then add 335 ml of laccase, stir at 550 rpm in an air atmosphere at 38° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 760 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) 8 g of enzyme-polymerized lignosulfonic acid, 1.5 g of citric acid and 230 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 13 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, and a direct current of 150 A was applied to prepare In at 1300 °C. 2 O 3 Powder, Ga 2 O3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 , Ga 2 O 3 , ZnO powder was mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%, and then 1.5 g of a modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 2 h, and the mixture was put into a horizontal high-energy sand mill and ground at 900 rpm for 3 h for wet grinding. During the grinding process, the slurry in the grinding chamber was subjected to ultrasonic bombardment with a power of 2000 W to obtain a composite slurry; (5) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (6) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (7) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0027] Comparative Example 5: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: (1) Dissolve sodium lignin sulfonate in deionized water, adjust the pH to 7, and obtain 100 ml of a 23% sodium lignin sulfonate solution. Then add 335 ml of laccase, stir at 550 rpm in an air atmosphere at 38° C., and continuously detect during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonic acid reaches 760 kDa. Then terminate the reaction, centrifuge, filter, dialyze, and freeze-dry to obtain the enzyme-polymerized lignin sulfonic acid. (2) 8 g of enzyme-polymerized lignosulfonic acid, 1.5 g of 1,2,3,4-butanetetracarboxylic acid and 230 ml of N,N-dimethylformamide were mixed and stirred evenly, and then 13 g of N,N'-dicyclohexylcarbodiimide and 2.5 g of 4-dimethylaminopyridine were added, reacted at room temperature for 48 h, vacuum filtered, precipitated in 1 M HCl aqueous solution, vacuum filtered and dried to obtain a modified surfactant; (3) Indium, gallium, and zinc were placed in a plasma reactor respectively. In a high-purity argon atmosphere, high-purity oxygen was introduced, the oxygen flow rate was controlled to 35 sccm, and a direct current of 150 A was applied to prepare In at 1300 °C. 2 O 3 Powder, Ga 2 O 3 Powder, ZnO powder, dried, and deagglomerated by air flow milling technology to obtain In with a particle size of 45nm 2 O 3 Powder,Ga 2 O 3 Powder, ZnO powder; (4) In 2 O 3 , Ga 2 O 3 , ZnO powder was mixed in a molar ratio of indium, gallium and zinc of 1:1:1, 500 ml of deionized water and 1 g of polyvinyl alcohol were added, and the mixture was stirred evenly to obtain a mixed slurry with a solid content of 60%, and then 1.5 g of a modified surfactant was added, and the mixture was stirred evenly and allowed to stand for 2 h, and the mixture was placed in a horizontal high-energy sand mill and ground at 900 rpm for 3 h for wet grinding to obtain a composite slurry; (5) The composite slurry was sprayed and granulated, with the atomizing disk speed of 7800 rpm, the inlet air temperature of 255°C, and the outlet air temperature of 115°C to obtain IGZO powder; (6) placing IGZO powder into a mold and pressing it to obtain a green embryo; wherein the pressure is 250 MPa; (7) The green embryo was sintered by first heating the temperature from room temperature to 730°C at a heating rate of 2.5°C / min, then heating the temperature to 1100°C at a heating rate of 1.3°C / min, and then sintering to 1330°C at a heating rate of 0.8°C / min, keeping the temperature for 21 h, and finally cooling the temperature from 1330°C to room temperature at a cooling rate of 4°C / min. In the range of 0-1100°C, oxygen was introduced at a flow rate of 10 L / min, and in the range of 1100-1350°C, air was introduced at a flow rate of 5 L / min. When cooling from 1350°C to room temperature, nitrogen was introduced at a flow rate of 20 L / min.

[0028] Comparative Example 6: A method for preparing a high-density, high-conductivity, low-resistivity IGZO target material, the specific steps are as follows: The difference from Example 2 is that the sintering method in step (7) is different, and the remaining steps are the same as Example 2; the sintering method of this comparative example is as follows: First, the temperature was raised from room temperature to 1320 °C at a heating rate of 5 °C / min, kept at that temperature for 4 h, and then cooled to room temperature. The entire sintering process was carried out in an air atmosphere.

[0029] Performance Testing Density: Test the actual density using the drainage method, and then calculate the density using the formula as follows: Density: The test was carried out using a density measuring instrument (Archimedes drainage method), and the test results are shown in Table 1; Grain size: tested using a metallographic microscope, the test results are shown in Table 1; Resistivity: tested with a four-probe resistance meter, the test results are shown in Table 1; Table 1 Performance test results Data analysis: It can be seen from Example 2 and Comparative Example 1 in Table 1 that by adopting the modified surfactant after grafting, the grafted composite material combines the steric hindrance effect of enzyme-polymerized wood sulfonic acid and the multi-functional group characteristics of 1,2,3,4-butanetetracarboxylic acid, and can form a more stable adsorption layer on the particle surface, providing a stronger dual effect of electrostatic repulsion and steric hindrance, thereby achieving a better dispersion effect and avoiding the problem of uneven distribution of enzyme-polymerized wood sulfonic acid and 1,2,3,4-butanetetracarboxylic acid in the slurry; and grafting can provide more nucleation sites, which can inhibit the excessive growth of grains. At the same time, grafting also enhances the binding force between enzyme-polymerized wood sulfonic acid and 1,2,3,4-butanetetracarboxylic acid, so that they can be more firmly attached to the particle surface, further improving the interface compatibility and adhesion, ensuring the uniform distribution of elements such as In, Ga, and Zn, and further improving the conductivity and density of the target material.

[0030] It can be seen from Example 2 and Comparative Example 2 in Table 1 that by adding enzyme-polymerized lignosulfonic acid and 1,2,3,4-butanetetracarboxylic acid to the slurry, on the one hand, the enzyme-polymerized lignosulfonic acid contains a large number of hydroxyl groups and sulfonic acid groups, which can interact with the surface of the IGZO powder to form a stable interface layer, which is conducive to the uniform dispersion and flow of the powder. On the other hand, the carboxyl group in the molecular structure of 1,2,3,4-butanetetracarboxylic acid can coordinate with the metal ions on the surface of the IGZO powder to form a stable complex, which is conducive to the molding of the powder and the formation of the internal hollow structure, so that the internal components of the formed powder are distributed more evenly, the number of non-conductive pores is reduced, and the density and conductivity of the target material are significantly improved, and the grain size is kept in a smaller range.

[0031] It can be seen from Example 2 and Comparative Example 3 in Table 1 that when the enzyme-polymerized lignin sulfonic acid is replaced by sodium lignin sulfonate, the conductivity and density of the target material are reduced to a certain extent. This is mainly because the enzyme-polymerized lignin sulfonic acid has a higher molecular weight, which can make the modified surfactant form a thicker and more stable adsorption layer on the particle surface, providing a stronger steric hindrance effect, thereby better preventing particle agglomeration. At the same time, compared with sodium lignin sulfonate, it retains more natural lignin structural characteristics while having a more complex chemical structure, which can provide more types of interaction sites, and enhance the interfacial compatibility and adhesion with IGZO particles.

[0032] It can be seen from Example 2 and Comparative Example 4 in Table 1 that by replacing 1,2,3,4-butanetetracarboxylic acid with citric acid, the conductivity and density of the target material are affected to a certain extent. This is mainly because 1,2,3,4-butanetetracarboxylic acid provides more reaction sites and stronger electrostatic repulsion than citric acid, which can more effectively disperse particles, prevent agglomeration, and provide a stronger steric hindrance effect; it can provide more nucleation sites, making it easier to cross-link with other molecules or particle surfaces to form a stable three-dimensional network structure, which can enable the modified surfactant to act as a bridge between IGZO particles, improve the interface compatibility and adhesion between the two, further promote the densification and homogenization process, and thus ensure the conductive performance.

[0033] It can be seen from Example 2 and Comparative Example 5 in Table 1 that during the wet grinding process, ultrasonic bombardment treatment is added, which can effectively break up powder agglomerates and promote uniform dispersion of powder, while also generating active sites on the particle surface, thereby increasing the binding force between particles and producing a certain synergistic effect with the modified surfactant, thereby jointly ensuring the conductive properties, density and small grain size of the target material.

[0034] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a high-density, high-conductivity, low-resistivity IGZO target, characterized in that: The following steps are involved: (1) dissolving sodium lignin sulfonate in deionized water and adjusting the pH to 7 to obtain a sodium lignin sulfonate solution, then adding laccase, stirring at 500-600 rpm in an air atmosphere at 37-40° C., continuously detecting during the reaction until the molecular weight of the enzyme-polymerized lignin sulfonate reaches 750-770 kDa, terminating the reaction, purifying, and obtaining the enzyme-polymerized lignin sulfonate; (2) Enzyme-polymerized lignosulfonic acid, 1,2,3,4-butanetetracarboxylic acid and N,N-dimethylformamide were mixed, stirred evenly, and N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added, reacted at room temperature for 48 hours, filtered, precipitated in 1M HCl aqueous solution, filtered, and dried to obtain a modified surfactant; (3) Indium, gallium and zinc are placed in a plasma reactor respectively, and In2O3 powder, Ga2O3 powder and ZnO powder are prepared by a direct current plasma method. After drying and depolymerization, In2O3 powder, Ga2O3 powder and ZnO powder are obtained; (4) In2O3 powder, Ga2O3 powder and ZnO powder are mixed, deionized water and dispersant are added, and the mixture is stirred evenly. Then, 0.5-2.5 g of modified surfactant is added and the mixture is allowed to stand for 1-2 h to obtain a mixed slurry. (5) placing the mixed slurry in a horizontal high-energy sand mill for wet grinding, and applying ultrasonic bombardment of 2000 W power to the slurry in the grinding chamber during the grinding process to obtain a composite slurry; (6) spray granulating the composite slurry to obtain IGZO powder; (7) Putting IGZO powder into a mold and pressing it to obtain a blank; (8) Sintering the green blank, first heating the temperature from room temperature to 700-750°C at a heating rate of 2-3°C / min, then heating the temperature to 1000-1100°C at a heating rate of 1-1.5°C / min, then sintering to 1320-1350°C at a heating rate of 0.7-0.9°C / min, keeping the temperature for 20-22h, and finally cooling the temperature from 1320-1350°C to room temperature at a cooling rate of 3-4°C / min, wherein oxygen is introduced at a flow rate of 10 L / min at 0-1100°C, air is introduced at a flow rate of 5 L / min at 1100-1350°C, and air is introduced at a flow rate of 20 L / min when cooling from 1350°C to room temperature. L / min nitrogen; the dosage ratio of the sodium lignin sulfonate solution and laccase in step (1) is 100ml:330-340ml; the dosage ratio of the enzyme-polymerized lignin sulfonic acid, 1,2,3,4-butanetetracarboxylic acid, N,N-dimethylformamide, N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step (2) is 5-10g:1-2g:200-250ml:10-15g:2-3g.

2. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The concentration of the sodium lignin sulfonate solution in step (1) is 20%-25%.

3. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The parameters of the DC plasma method in step (3) are as follows: in a high-purity argon atmosphere, high-purity oxygen is introduced, the oxygen flow rate is controlled to be 30-40 sccm, a DC current of 100-200 A is applied, and the temperature is 1000-1500°C.

4. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The depolymerization in step (3) is carried out by using air flow pulverization technology.

5. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The amount of In2O3 powder, Ga2O3 powder and ZnO powder added in step (4) is based on a molar ratio of indium, gallium and zinc of 1:1:

1.

6. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The dispersant in step (4) is one of polyvinyl alcohol and polyethylene glycol, and the added amount is 0.1%-0.25% of deionized water. The modified surfactant in step (4) is added in an amount of 0.1%-0.5% of deionized water.

7. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The ball milling speed of the wet grinding in step (5) is 800-1000 rpm, and the ball milling time is 2-3 h.

8. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The parameters of the spray granulation in step (6) are: atomizing disk speed 7500-8000 rpm, air inlet temperature 250-260°C, and air outlet temperature 110-120°C.

9. The method for preparing a high-density, high-conductivity, low-resistivity IGZO target according to claim 1, characterized in that: The pressing pressure in step (7) is 200-300 MPa.

10. A high-density, high-conductivity, low-resistivity IGZO target material, characterized in that: The high-density, high-conductivity, low-resistivity IGZO target material is prepared according to the method for preparing the high-density, high-conductivity, low-resistivity IGZO target material according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of IGZO target material

    CN117105636A